Costs of climate change: The effects of rising temperatures on health and productivity - Michael Hübler; Gernot Klepper; Sonja Peterson (Kiel Institute for the World Economy (IfW), 2007)
The aim of the study is to quantify climate induced health risks for Germany. Based on high resolution climate scenarios for the period 2071 to 2100 we forecast the number of days with heat load and cold stress. The heat frequency and intensity increases overall but more in the south. Referring to empirical studies on heat induced health effects we estimate an average increase in the number of heat induced casualties by a factor of more than 3. Heat related hospitalization costs increase 6-fold not including the cost of ambulant treatment. Heat also reduces the work performance resulting in an estimated output loss of between 0.12 % and 0.48 % of GDP.
Older version: http://hdl.handle.net/10419/3993
Keywords: I10; Q51; Q54; 330; costs of climate change; health effects; heat waves; mortality; hospitalization costs; labor productivity; Klimawandel; Soziale Kosten; Prognose; Gesundheit; Gesundheitskosten; Arbeitsproduktivität; Welt